Care of adolescents and young adults with cancer in Asia: results of an ESMO/SIOPE/SIOP Asia survey. Issue 3 (6th June 2019) - Li, Chi Kong; Dalvi, Rashmi; Yonemori, Kan; Ariffin, Hany; Lyu, Chuhl Joo; Farid, Mohamad; Gonzales-Santos, Julieta Rita N; Zhou, Qing; Bielack, Stefan; Brugieres, Laurence; Blondeel, Anne; Essiaf, Samira; et al.
Abstract : Background: Adolescents and young adults (AYAs) with cancer require dedicated management encompassing both adult and paediatric cancer services. Following a European survey, the European Society for Medical Oncology, the European Society for Paediatric Oncology and the Asian continental branch of International Society of Paediatric Oncology undertook a similar survey to assess AYA cancer care across Asia. Methods: A link to the online survey was sent to healthcare professionals (HCPs) in Asia interested in AYA cancer care. Questions covered the demographics and training of HCPs, their understanding of AYA definition, availability and access to specialised AYA services, the support and advice offered during and after treatment, and factors of treatment non-compliance. Results: We received 268 responses from 22 Asian countries. There was a striking variation in the definition of AYA (median lower age 15 years, median higher age 29 years). The majority of the respondents (78%) did not have access to specialised cancer services and 73% were not aware of any research initiatives for AYA. Over two-thirds (69%) had the option to refer their patients for psychological and/or nutritional support and most advised their patients on a healthy lifestyle. Even so, 46% did not ask about smokeless tobacco habits and only half referred smokers to a smoking cessation service. Furthermore, 29% did not promote human papillomavirus vaccination for girls and 17% did not promote hepatitis B virus vaccination for high-risk individuals. In terms of funding, 69% reported governmental insurance coverage, although 65% reported that patients self-paid, at least partially. Almost half (47%) reported treatment non-compliance or abandonment as an issue, attributed to financial and family problems (72%), loss of follow-up (74%) and seeking of alternative treatments (77%). Conclusions: Lack of access to and suboptimal delivery of AYA-specialised cancer care services across Asia pose major challenges and require specific interventions.